Prediction of Gene Expression Patterns With Generalized Linear Regression Model - Liu, Shuai; Lu, Mengye; Li, Hanshuang; Zuo, Yongchun (Frontiers in Genetics, 2019)
Cell reprogramming played important roles in medical science, such as tissue repair, organ reconstruction, disease treatment, new drug development and breeding of new species. Especially, Oct4, the core pluripotency factor, played a key role in somatic cell reprogramming through transcriptional control. However, there was no scientific description of quantitative relationship between Oct4 signal intensity and target gene expression currently. Therefore, a generalized linear regression method was constructed to predict gene expression values by applying Oct4 signal intensity in promoter regions. Experimental data, including Oct4 signal intensity and target gene expression, were from eight typical genes with different cell development stages in promoter regions. Besides, quantitative relationship between gene expression and Oct 4 signal intensity was analyzed with the proposed model. Experimental results showed that our proposed method can achieve 78% goodness of fit with 90% confidence, which denoted partly relationship between Oct4 signal intensity and gene expression.